The Role of Positivity in Enhancing the Relationship Between Social Support and Subjective Well-being - Fatimah, Malida; Paramastri, Ira; Rinaldi, Martaria Rizky; Gani, Nasfira binti Che Abdul (Universitas Ahmad Dahlan, 2025)
University students often encounter various academic and personal challenges that may affect their psychological functioning. Subjective well-being is a crucial psychological resource that helps individuals cope with these challenges. Among the key factors influencing subjective well-being are social support and positivity. This study examines the moderating role of positivity in the relationship between social support and subjective well-being. Using a quantitative correlational design, data were collected from 416 university students through three validated instruments: the Social Support Scale, the Positivity Scale, and the Subjective Well-being Scale. The data were analyzed using moderated regression analysis. Results revealed that social support and positivity were positively and significantly associated with subjective well-being. Moreover, positivity significantly moderated the relationship between social support and subjective well-being. The simple slope analysis shows that at a high positivity level (+1 SD), the estimated effect of social support on subjective well-being was 0.296 (SE = 0.0344, Z = 8.62, p < 0.001). This shows that positivity strengthens the relationship between social support and subjective well-being.